Comparative analysis of power smoothing control strategies for grid-connected photovoltaic systems - Low, Ryan Yew Meng (Nanyang Technological University, 2024)
Due to the projected depletion of fossil fuels in the coming century, it is crucial for us to find an alternative source of energy. An alternative source of energy includes clean energy. There are many types of clean energy, namely solar photovoltaic (PV) power, wind energy, hydropower and many more. The advantages of clean energy are mainly its abundance and pollution free qualities. The use of PV power is considered in this project as solar PV is readily available if there is sunlight. Additionally, it is widely implemented and contributes significantly to the clean energy production. Therefore, it is critical for us to investigate the comparison of multiple power ramp rate control (PRRC) methods.